Cohort profile: the Viral load Cohort North-East Lesotho (VICONEL) from 2016 to 2023 – cohort description, test volumes, predictors of viraemia and the road ahead - Tracy Glass; Frédérique Chammartin; Jochen Ehmer; Thomas Klimkait; Alain Amstutz; Josephine Muhairwe; Irene Ayakaka; Blaise Lukau; Jennifer Anne Brown; Lipontso Motaboli; Malebanye Lerotholi; Maurus Kohler; et al. (BMJ Open)
Purpose The prospective Viral load Cohort North-East Lesotho (VICONEL) aims to support clinical management and generate scientific evidence to inform HIV care. Specifically, VICONEL allows for the monitoring of HIV treatment outcomes and health system performance, encompasses a biobank for further research with routinely collected blood plasma samples of consenting participants and provides a valuable framework for nested observational and interventional studies.Participants VICONEL captures routine viral load test results alongside associated demographic and treatment information among people in care for HIV in Lesotho, southern Africa. As of December 2023, it encompasses all viral load testing from 24 healthcare facilities in two districts of Lesotho.Findings to date From January 2016 to December 2023, 137 660 viral load test results were available for 29 380 participants. At the time of the last viral load test, median age was 42 years (IQR: 33–53); 18 511 (63%) were adult women, 10 029 (34%) adult men and 835 (3%) children <15 years (age/sex missing for 5) and median time taking antiretroviral therapy (ART) was 6.4 years (IQR 3.2–9.9). Overall, the proportion of cohort participants with viral suppression to <1000 copies/mL has continually exceeded 90% and has been above 95% since 2020; however, this proportion has consistently been lower among children. Sex, age category/ART regimen core agent (combined variable), time since ART initiation and district were independently associated with viraemia.Future plans VICONEL offers potential for (1) further digitalisation and automation of results sharing at the client, facility and district/national level, (2) integration of additional clinical and diagnostic data, including comorbidities and drug resistance and (3) embedding randomised trials.